Biblioteki i media w czasie pandemii COVID-19. Bibliografia selektywna (od września 2021 do marca 2022 roku) - Kowalska, Marzena (Acta Universitatis Lodziensis. Folia Librorum, 2022)
Selective bibliography of monographies and articles from representative scientific and professional journals in the field of information science and book science as well as social communication and media, which were published in Poland between November 2021 and march 2022.